1999
DOI: 10.1074/jbc.274.11.6865
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of the Oxygen-linked Interaction Energy for Inositol Hexakisphosphate and Bezafibrate Binding to Human HbA0

Abstract: The energetics of signal propagation between different functional domains (i.e. the binding sites for O 2 , inositol hexakisphospate (IHP), and bezafibrate (BZF)) of human HbA 0 was analyzed at different heme ligation states and through the use of a stable, partially heme ligated intermediate. Present data allow three main conclusions to be drawn, and namely: (i) IHP and BZF enhance each others binding as the oxygenation proceeds, the coupling free energy going from close to zero in the deoxy state to ؊3.4 kJ/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…Our current functional data on the R-state-locked hemoglobin with and without BZF are consistent at least qualitatively with recent oxygen equilibrium studies of human hemoglobin (19,20) showing that the addition of BZF to stripped hemoglobin lowers the oxygen affinity of R-state hemoglobin by a factor of 8 -10 at pH 7.0.…”
Section: Structure Of Carbonmonoxyhemoglobin-bezafibrate Complex 38794supporting
confidence: 76%
See 1 more Smart Citation
“…Our current functional data on the R-state-locked hemoglobin with and without BZF are consistent at least qualitatively with recent oxygen equilibrium studies of human hemoglobin (19,20) showing that the addition of BZF to stripped hemoglobin lowers the oxygen affinity of R-state hemoglobin by a factor of 8 -10 at pH 7.0.…”
Section: Structure Of Carbonmonoxyhemoglobin-bezafibrate Complex 38794supporting
confidence: 76%
“…Ala E6(␣57) and Leu E17(␣68), that are substituted by Gly and Asn, respectively. Furthermore, several lines of evidence indicate that BZF binds specifically to fully liganded R-state human hemoglobin in a functionally relevant way (17)(18)(19)(20). We do not yet fully understand the reason why the previous solution binding studies found only a nonspecific binding of BZF with human carbonmonoxyhemoglobin (11,12).…”
Section: Structure Of Carbonmonoxyhemoglobin-bezafibrate Complex 38794mentioning
confidence: 58%
“…Since the O 2 affinity is no longer directly related to the T/R quaternary states, there is no basis to assign any low affinity behaviors solely to the T state. Available kinetic data of low ligand affinity characteristics of ligated Hb in the presence of potent heterotropic effectors (30,31) indicates that kinetic techniques alone cannot distinguish low affinity behaviors of T-state Hb from those of R-state Hb. Coletta et al (31) integrated their kinetic, thermodynamic, and structural data and came to a conclusion that the observed low affinity kinetic behaviors of ligated (oxy and carbonmonoxy) Hb in the presence of BZF ϩ IHP at pH 7.0 are derived from the effectorinduced low affinity state of R (ligated) Hb.…”
Section: Figmentioning
confidence: 99%
“…Available kinetic data of low ligand affinity characteristics of ligated Hb in the presence of potent heterotropic effectors (30,31) indicates that kinetic techniques alone cannot distinguish low affinity behaviors of T-state Hb from those of R-state Hb. Coletta et al (31) integrated their kinetic, thermodynamic, and structural data and came to a conclusion that the observed low affinity kinetic behaviors of ligated (oxy and carbonmonoxy) Hb in the presence of BZF ϩ IHP at pH 7.0 are derived from the effectorinduced low affinity state of R (ligated) Hb. This is in full agreement with our present interpretation and is a direct contrast to the solely kinetics-based interpretation of Marden et al (30).…”
Section: Figmentioning
confidence: 99%
“…For example, the binding of BZF or IHP to CO-Hb complex decreases the CO association rate approximately four or eight times, respectively (Marden et al, 1990), and decreases the affinity of R state deoxy-Hb for oxygen . Coletta et al (1999a) have reported the α-and β-chain (Song et al, 2008).…”
Section: Discussionmentioning
confidence: 99%